2009
DOI: 10.1177/1545109709332469
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution Inflammatory Syndrome in a Resource-Poor Setting

Abstract: The immune reconstitution inflammatory syndrome (IRIS) associated with highly active antiretroviral therapy (HAART) was studied in rural Ethiopian HIV-infected patients. Review of 1002 charts in an outpatient clinic was conducted. The median CD4 count was 89 cells/mm3. Ninety-eight patients were hospitalized after initiation of HAART, of whom 74 were hospitalized for manifestations of IRIS (ie, 7% of patients on HAART). Of the 74 patients hospitalized with IRIS, 27 patients had tuberculosis; 12 patients, crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Our very high prevalence could be biased; since our institution is a tertiary-care center receiving patients with more extended KS disease [31]. The median time to development of KS-IRIS was 10 weeks, similar to the previously reported 6–14 week lapse after cART initiation [17, 19, 26, 33, 34]. IRIS associated to other pathogens (i.e., cytomegalovirus, MTB, MAC, and hepatitis B) has been reported to occur earlier within 2–5 weeks after cART initiation [3335].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our very high prevalence could be biased; since our institution is a tertiary-care center receiving patients with more extended KS disease [31]. The median time to development of KS-IRIS was 10 weeks, similar to the previously reported 6–14 week lapse after cART initiation [17, 19, 26, 33, 34]. IRIS associated to other pathogens (i.e., cytomegalovirus, MTB, MAC, and hepatitis B) has been reported to occur earlier within 2–5 weeks after cART initiation [3335].…”
Section: Discussionsupporting
confidence: 72%
“…IRIS has been reported to occur in 10‒30% of antiretroviral-naïve patients with a 5–30% mortality rate [5, 16]. In Africa, it has become a significant cause of morbidity and mortality in HIV-infected patients with access to cART [5, 17, 18]. IRIS has been described in association with different infectious processes [10, 1921].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from South Africa and Ethiopia estimate an incidence of 7%–33% 171173. Paradoxical IRIS also affects solid organ-transplant patients when antirejection medications are interrupted during CM therapy,141 and apparently healthy hosts may suffer from reactivation of immune defenses that were previously overwhelmed by high fungal burden.…”
Section: Additional Therapeutic Considerationsmentioning
confidence: 99%
“…A similar study done in the Dessie Referral Hospital determined that *3% of patients with TB-IRIS had severe-enough disease to be hospitalized. 18 Our current study in the same institution revealed that 7% or 143 patients of 1977 outpatients initiating ART developed TB-IRIS within 6 months of beginning ART. A low baseline CD4 count at the initiation ART and a history of WHO Clinical Stage 3 or 4 were identified as independent risk factors.…”
Section: Discussionmentioning
confidence: 55%